Understanding Circle Time Practices in Montessori Early Childhood Settings - Andrea Koczela; Kateri Carver (University of Kansas, 2023)
Circle time is commonplace in traditional preschools, yet there are few references to the practice in Montessori's writings or in major Montessori organizations' and teacher education standards. This article investigates whether circle time is frequent in Montessori 3-6-year-old classrooms using data from a widely distributed Qualtrics survey. The results, from 276 respondents spanning all 50 states, provide insight into the circle time practices of United States-based preschool Montessori teachers, also known in Montessori classrooms as guides. We present novel information regarding circle time duration and frequency, types of circle time activities, Montessori guides' circle time training and planning, whether children's circle time attendance is free choice or compulsory, and the nature of circle time in programs associated with Association Montessori Internationale versus American Montessori Society. Results revealed that 92% of survey participants have circle time every day or most days; most participants hold circle time for 20 minutes or less; the most common circle time events were show-and-tell, calendar work, vocabulary lessons, Grace and Courtesy lessons, read aloud discussions, dancing and movement, snack time, general conversation, read aloud (stories), and birthday celebrations. We found that many of the most frequent circle time activities do not align with children's preferences, teacher preferences, or Early Childhood best practices. Our work invites Montessorians to engage in the work of reconstructing the traditional practice of circle time to better align with Montessori hallmarks of choice, development of the will, and joyfulness.